Prevalence and risk factors of osteoarthritis in patients at a public hospital in Limpopo province - Tsundzuka Masangu; Boikhutso Tlou; Thembelihle Dlungwane (South African Family Practice)
Background: Osteoarthritis (OA) is a public health concern affecting millions globally. Osteoarthritis has been ranked as the 12th leading cause of disability among the ageing population globally. In addition, OA can lead to disability, which can affect the quality of life and physical and emotional well-being.